Neurogenic Lower Urinary Tract Dysfunction in the First Year After Spinal Cord Injury: A Descriptive Study of Urodynamic Findings. Issue 1 (20th January 2023) - Kozomara, Marko; Birkhäuser, Veronika; Anderson, Collene E.; Bywater, Mirjam; Gross, Oliver; Kiss, Stephan; Knüpfer, Stephanie C.; Koschorke, Miriam; Leitner, Lorenz; Mehnert, Ulrich; Sadri, Helen; Sammer, Ulla; et al.
Abstract : Purpose: We aimed to provide a real-world description of neurogenic lower urinary tract dysfunction within the first year after spinal cord injury with a focus on unfavorable urodynamic parameters that are associated with urological morbidity. Materials and Methods: Urodynamic investigations from 97 patients with traumatic or ischemic acute spinal cord injury and managed according to the European Association of Urology Guidelines on Neuro-Urology were analyzed at a single university spinal cord injury center at 1 month, 3 months, 6 months, and 12 months after injury. Unfavorable urodynamic parameters were defined as detrusor overactivity in combination with detrusor sphincter dyssynergia, maximum storage detrusor pressure of 40 cm H2 O or higher, bladder compliance less than 20 mL/cm H2 O, and vesicoureteral reflux of any grade. Results: One or more unfavorable urodynamic parameter was observed in 87 out of 97 patients (90%) within the first year after spinal cord injury. Eighty-eight percent of the patients showed detrusor overactivity with detrusor sphincter dyssynergia, 39% a maximum storage detrusor pressure of 40 cm H2 O or higher, and 7% vesicoureteral reflux. No patient developed a low-compliance bladder. Conclusions: Using a standardized urodynamic follow-up schedule, we found unfavorable urodynamic parameters in a majority of the population within the first year after spinal cord injury. As early treatment based on urodynamic findings might reduce the risk of deterioration of upper and lower urinary tract function, thereby improving long-term outcomes, there is need for further research regarding recommendations for a urodynamic follow-up schedule during the first year after spinal cord injury.